If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + 7(m + 7) = 89 Reorder the terms: 3m + 7(7 + m) = 89 3m + (7 * 7 + m * 7) = 89 3m + (49 + 7m) = 89 Reorder the terms: 49 + 3m + 7m = 89 Combine like terms: 3m + 7m = 10m 49 + 10m = 89 Solving 49 + 10m = 89 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-49' to each side of the equation. 49 + -49 + 10m = 89 + -49 Combine like terms: 49 + -49 = 0 0 + 10m = 89 + -49 10m = 89 + -49 Combine like terms: 89 + -49 = 40 10m = 40 Divide each side by '10'. m = 4 Simplifying m = 4
| 2n^2+2=10n | | 4c^3-1c=0 | | 9-16+6x=11x+4x-5 | | 4u+5u+4u=p+q | | 3x^2-21x^6=0 | | Y-1=4y-10 | | 3(-5)+2=5 | | X^2-5p=0 | | 2x^4+5x^2-12=0 | | 5/8-(5/6) | | 17x^2-12xy+8y^2-22x-4y+14=0 | | 3(x+y)-r=2y | | B^2-2b+7=0 | | 2z=14-20 | | 4x-30+3x=180 | | 12x-14=70+9x | | X-1/6=23/6 | | y(n)-0.5y(n-1)=x(n)+x(n-1) | | -54-17x=90-14x | | 12x-14=50+9x | | (x^4/8)^3 | | 108-2x=4y | | 2y+3=-3y-7 | | m^2+16m+4=0 | | P+4t=9t | | 1-10n+9n-1= | | (4x^2)+6x=5 | | a(n-2)+3=bn | | 108-2x/4 | | -30-(-20)=x/11 | | 4m+3=6 | | -6x+8y=-36 |